1984
DOI: 10.1055/s-2007-969682
|View full text |Cite
|
Sign up to set email alerts
|

Components of Root Bark ofCudrania tricuspidatal.1,2Structures of Four New Isoprenylated Xanthones, Cudraxanthones A, B, C and D

Abstract: Four new isoprenylated xanthones, cudraxanthones A, B and C were isolated from the N-hexane extract of the root bark of CUDRANIA TRICUSPIDATA (Carr.) Bur. (Japanese name "Hariguwa"; Moraceae), and cudraxanthone D from the benzene extract. The structures of cudraxanthones A, B, C and D were shown to be 1-4, respectively, on the basis of spectral and chemical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The structures of isolated compounds were identified as euchrestaflavanone C (1), 9) gerontoxanthone A (2), 10) cudraxanthone B (3), 11) cudraflavone B (4), 12) gericudranin E (5), 13) cudraxanthone C (7), 11) and cudraxanthone H (8), 14) respectively, by comparing UV, (Table 1), including one carbonyl group, two aromatic rings with six oxygenated carbons, and two C 5 groups, corresponding to a diprenylated and tetrahydroxylated xanthone. The positions of the substituents on the ring system were determined on the basis of HMBC correlations, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of isolated compounds were identified as euchrestaflavanone C (1), 9) gerontoxanthone A (2), 10) cudraxanthone B (3), 11) cudraflavone B (4), 12) gericudranin E (5), 13) cudraxanthone C (7), 11) and cudraxanthone H (8), 14) respectively, by comparing UV, (Table 1), including one carbonyl group, two aromatic rings with six oxygenated carbons, and two C 5 groups, corresponding to a diprenylated and tetrahydroxylated xanthone. The positions of the substituents on the ring system were determined on the basis of HMBC correlations, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the presence of two chromene rings was observed from the signals at [δ H 8.18 (1H, d, J = 10.4 Hz), 5.92 (1H, d, J = 10.0 Hz), 1.47 (6H, s); δ C 121.0, 132.3, 75.7, 26.3] and [δ H 6.57 (1H, d, J = 10.0 Hz), 5.87 (1H, d, J = 10.0 Hz), 1.50 (6H, s); δ C 121.6, 131.2, 77.5, 27.4], which were supported by HSQC and HMBC correlations. The position of one chromene ring was determined to be C‐1 from the HMBC correlations between H‐12 to C‐1 and H‐3 to C‐2 together with the downfielded proton signal of H‐11 at δ H 8.18 due to adjacent carbonyl group (C‐9) . The position of the other chromene ring was determined to be C‐7 from the HMBC correlations between H‐16 to C‐6, C‐8, and H‐17 to C‐7, which was supported by the NOESY correlation between H‐16 to H‐8.…”
Section: Resultsmentioning
confidence: 85%
“…Taken together, compound 29 was determined as shown and named cudracuspixanthone F. Compound 5, 27.4], which were supported by HSQC and HMBC correlations. The position of one chromene ring was determined to be C-1 from the HMBC correlations between H-12 to C-1 and H-3 to C-2 together with the downfielded proton signal of H-11 at d H 8.18 due to adjacent carbonyl group (C-9) [20]. The position of the other chromene ring was determined to be C-7 from the HMBC correlations between H-16 to C-6, C-8, and H-17 to C-7, which was supported by the NOESY correlation between H-16 to H-8.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the root bark and cortex of this species have been used in traditional medicine for the therapy of inflammation and neuritis [ 2 ]. Previous phytochemical research has shown that C. tricuspidata contains several components such as xanthones [ 3 ], flavonoids [ 4 ], and glycoproteins [ 5 ]. In recent studies of the pharmacological effects of this plant, C. tricuspidata extracts have been shown to have various biological effects, including hepatoprotective [ 6 ], antioxidant [ 7 ], monoamine oxidase-A inhibitory [ 8 ], neuroprotective [ 9 ], anti-atherosclerotic, and anti-inflammatory activities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%